Bettering Academic Services through the Use of an Integrated Academic Information System - Hartinah, Hartinah; Aras, Suhardi; Nugroho, Moch Nur Syawalludin; Mutmainna, Mutmainna; Jafar, Lili Septiani (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2024)
Nowadays, humans cannot be separated from information technology; this significantly impacts various fields, especially educational administration. Academic services that were initially manual have now transformed into digital, where academic data, both information and other administration, can now be handled by information systems. This study aimed to determine the effectiveness of implementing the integrated academic information system (SIAT) that has been running in Islamic universities. Data collection was carried out using a descriptive qualitative method concerning the field research approach combined with data triangulation; data collection was obtained by distributing questionnaires, qualitative interviews, and observations. The findings were that SIAT could increase the effectiveness and efficiency of academic services at the Faculty, ease of accessing information, especially in KRS filling activities, KHS checking, lecture monitoring, lecturer grade input, and distribution of lecture schedules can be done in one system. The obstacles felt were few, especially if the system was undergoing maintenance, data loading was hampered, and some students did not understand how to operate the information system. The solution that can be done is to hold periodic socialization regarding the implementation of SIAT and to update the system so that it remains optimal in its operation.